The effect of exposure to radiofrequency electromagnetic fields on cognitive performance in human experimental studies: A protocol for a systematic review. (December 2021) - Pophof, Blanka; Burns, Jacob; Danker-Hopfe, Heidi; Dorn, Hans; Egblomassé-Roidl, Cornelia; Eggert, Torsten; Fuks, Kateryna; Henschenmacher, Bernd; Kuhne, Jens; Sauter, Cornelia; Schmid, Gernot
Abstract: Background: The World Health Organization (WHO) is currently assessing the potential health effects of exposure to radiofrequency electromagnetic fields (RF-EMFs) in the general and working population. Related to one such health effect, there is a concern that RF-EMFs may affect cognitive performance in humans. The systematic review (SR) aims to identify, summarize and synthesize the evidence base related to this question. Here, we present the protocol for the planned SR. Objectives: The main objective is to present a protocol for a SR which will evaluate the associations between short-term exposure to RF-EMFs and cognitive performance in human experimental studies. Data sources: We will search the following databases: PubMed, Embase, Web of Science, Scopus, and the EMF-Portal. The reference lists of included studies and retrieved review articles will be manually searched. Study eligibility and criteria: We will include randomized human experimental studies that assess the effects of RF-EMFs on cognitive performance compared to no exposure or lower exposure. We will include peer-reviewed articles of any publication date in any language that report primary data. Data extraction and analysis: Data will be extracted according to a pre-defined set of forms developed and piloted by the review author team. To assess the risk of bias, we will apply the Rating Tool for Human and Animal Studies developed by NTP/OHAT, supplemented with additional questions relevant for cross-over studies. Where sufficiently similar studies are identified (e.g. the heterogeneity concerning population, exposure and outcome is low and the studies can be combined), we will conduct random-effects meta-analysis; otherwise, we will conduct a narrative synthesis. Assessment of certainty of evidence: The certainty of evidence for each identified outcome will be assessed according to Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Performing the review according to this protocol will allow the identification of possible effects of RF-EMFs on cognitive performance in humans. The protocol has been registered in PROSPERO, an open-source protocol registration system, to foster transparency.